Pengaruh Good Corporate Governance, Intellectual Capital dan Leverage Terhadap Nilai Perusahaan - Melansari Siti Nurtiara; H.M. Taufik Aziz; Merry Sukartini (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
This study aims to analyze the influence of Good Corporate Governance (GCG), intellectual capital, and leverage on firm value in technology sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. GCG is measured through three indicators: managerial ownership, institutional ownership, and the presence of an audit committee. Intellectual capital is measured using the Value Added Intellectual Coefficient (VAIC™) method, while leverage is measured using the Debt to Equity Ratio (DER). Firm value as the dependent variable is measured using the Tobin's Q ratio. This study uses a quantitative approach with secondary data obtained from annual reports and financial statements of companies accessed through the official IDX website and each company's website. A purposive sampling technique was used to determine the sample, and eight companies were obtained with a total of 32 observation data over a four-year period. The results show that leverage has a significant effect on firm value, indicating that appropriate and proportional debt structure management is a key factor in increasing the value of companies in the technology sector. Meanwhile, managerial ownership, institutional ownership, the presence of an audit committee, and intellectual capital did not show a significant effect on firm value. This suggests that, in the technology sector, external financing strategies play a greater role than internal company factors such as ownership structure and intangible assets. These findings are expected to serve as a reference for company management and investors in formulating financing policies and managing knowledge-based resources.